Blockchain revolution : - Tapscott, Don (Portfolio/​Penguin, 2018)
In Blockchain Revoltuion, Don and Alex Tapscott bring us a researched, accessible and essential book about the technology driving the future of the economy. Blockchain is the ingeniously simple, revolutionary protocol that allows transactions to be simultaneously anonymous and secure by maintaining a tamperproof public ledger of value. Though it's best known as the technology that drives bitcoin and other digital currencies, it also has the potential to record virtually everything of value to humankind, from birth and death certificates to insurance claims, land titles and even votes. As with any paradigm shift, blockchain technology will create winners and losers. This book shines a light on where it can lead us in the next decade and beyond.